Extremum seeking control for truck drag reduction - Papageorgiou, Georgios; Barden, Jason; Whidborne, James F.; Garry, Kevin P. (Cranfield University, 2018)
The aerodynamic drag on a heavy truck tractor and semi-trailer combination can be reduced by means of a wind deflector installed on the roof of the tractor cab. The drag reduction is dependent upon the height and shape of the deflector. A variable height deflector has been constructed and tested in a wind-tunnel and on-road. In this paper, an extremum-seeking control scheme is proposed to adjust on-line the deflector height to minimize the aerodynamic drag. The effectiveness of the scheme is evaluated by simulation and its practicality is evaluated.